Museum in the Countryside: Aesthetics of the Data Centre - Koolhaas, Rem (Architectural design, 2019)
As part of OMA's forthcoming exhibition ‘Countryside: Future of the World’, which opens at the Solomon R Guggenheim Museum in New York this autumn, the office is cataloguing the emergence of a new kind of architecture, the data centre. These vast, monolithic facilities are not designed to be inhabited by humans, but through their unimaginable scale and radical starkness they illicit the sensibilities of a new technological sublime. OMA founder Rem Koolhaas explores the ways through which architects might be able to engage this condition through cultural programmes and make it accessible to the people it would otherwise exclude.